Early plans as source materials to study the urban past = Dawne plany jako materiały źródłowe do badań nad przeszłością miast - Nieścioruk, Kamil (Instytut Archeologii i Etnologii Polskiej Akademii Nauk, 2012)
The paper addresses the problem of establishing a comprehensive approach to using and analysing historic city plans, a key cartographic source material for studying the urban past. An approach structured around four stages is presented and it is stressed that none can be omitted. The main part deals with the importance of understanding the geometric qualities of early cartography and its limitations. The role of GIS as a tool to georeference early plans and to re-create virtual past landscapes in 3D is also shown. The importance of an interdisciplinary approach to early map analyses and research (beside comprehensive one) is also discussed.
ill. ; 25 cm
Keywords: early plans; cartography; GIS; historical GIS; comprehensive research